2013
DOI: 10.1021/jp310045g
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Strain Energy Effects in Faceted Decahedral Nanoparticles

Abstract: Decahedral morphology, with re-entrant surface modifications, is one of the common structures observed in nanoparticles. These motifs, although thermodynamically stable only at very small size ranges, have been experimentally observed to grow up to much larger sizes (100 nm to several micrometers). Whereas the surface energy plays an important role, the contributions of the elastic strain energy are nonnegligible at larger sizes and the effect of stress relaxation due to re-entrant surface faceting is poorly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 44 publications
6
66
0
Order By: Relevance
“…6 shows that the nanoparticle has steps, wedges in the corners and complicated rough surface is consistent with a structure produced by the kinetics as recently discussed by (Patala et al, 2013). The steps with kinks correspond to the morphology obtained by growth by step movement, i.e., atoms are added to the steps which provoke their movement, which is a classical mechanism for crystal growth.…”
Section: Discussionsupporting
confidence: 84%
“…6 shows that the nanoparticle has steps, wedges in the corners and complicated rough surface is consistent with a structure produced by the kinetics as recently discussed by (Patala et al, 2013). The steps with kinks correspond to the morphology obtained by growth by step movement, i.e., atoms are added to the steps which provoke their movement, which is a classical mechanism for crystal growth.…”
Section: Discussionsupporting
confidence: 84%
“…The model shown in Fig. 3.14b shows that the nanoparticle has steps, wedges in the corners, and complicated rough surface which is consistent with a structure produced by the kinetics, as has been recently discussed by Patala et al [ 76 ]. The steps with kinks correspond to the morphology obtained by growth by step movement, i.e., atoms are added to the steps which provoke their movement; this is a classical mechanism of crystal growth.…”
Section: Holographysupporting
confidence: 81%
“…The subscript i and t subscripts refer to certain facets and the twin boundary, respectively . Their finite element analysis revealed that a balance between surface energy and volumetric strain energy accounts for different decahedral shapes at different particle sizes . At smaller sizes, WVD of the NC is small, and the free energy is dominated by the surface energy term, favoring convex decahedra.…”
Section: Resultsmentioning
confidence: 99%